Improving Seismic Performance of RC Structures with Innovative TnT BRBs: A Shake Table and Finite Element Investigation - Evrim Oyguc; Resat Oyguc; Onur Seker; Abdul Hayir; Jay Shen; Bulent Akbas (Applied Sciences)
Addressing the critical seismic vulnerabilities of reinforced concrete (RC) beam-column joints remains an imperative research priority in earthquake engineering. This study presents an experimental and analytical investigation into the seismic performance enhancement of non-ductile RC frames using an innovative all-steel Tube-in-Tube Buckling-Restrained Brace (TnT BRB) system. Shake table tests were performed on one-third scale RC frame specimens, including a baseline structure representing conventional substandard design and a counterpart retrofitted with the proposed TnT BRBs. Experimental results revealed that the unretrofitted specimen experienced pronounced brittle shear failures, excessive lateral deformations, and significant degradation of beam-column joints under cyclic seismic loading. In contrast, the TnT BRB-retrofitted specimen exhibited substantially improved seismic behavior, characterized by enhanced energy dissipation, controlled inter-story drifts, and preserved joint integrity. Advanced fiber-based finite element modeling complemented the experimental efforts, accurately capturing critical nonlinear phenomena such as hysteretic energy dissipation, stiffness degradation, and localized damage evolution within the structural components. Despite inherent modeling limitations regarding bond-slip effects and micro-level cracking, strong correlation between numerical and experimental results affirmed the efficacy of the TnT BRB retrofit solution. This integrated experimental-analytical approach offers a robust, cost-effective pathway for upgrading seismically deficient RC structures in earthquake-prone regions.